Pemijahan Ikan Endemik Pelangi Arfak (Melanotaenia Arfakensis) Secara Alami - Mofu, Vicky Arnold; Pranata, Bayu; Manaf, Marhan (Proceedings Series on Physical & Formal Sciences, 2021)
Arfak rainbowfish (Melanotaenia arfakensis) is one of the endemic fish of West Papua that can be found in river and lake systems in the Manokwari Regency. Currently, the status of the arfak rainbowfish is nearly extinct. Therefore, this study aimed to know the hatching rate and survival of arfak rainbowfish larvae that were naturally spawned. The results showed that the hatchability of arfak rainbowfish eggs reached 96.9% in A1 aquarium and 96.4% in A2 aquarium. The survival rate of arfak rainbowfish larvae in the A1 aquarium was 67.5%, while the A2 aquarium was 58.7%. The larval survival rate was relatively low. Therefore, further research is needed to increase the survival rate of arfak rainbowfish larvae.